2023
DOI: 10.3390/ijerph20054126
|View full text |Cite
|
Sign up to set email alerts
|

Life Habits of Healthcare Professionals during the Third Wave of COVID-19: A Cross-Sectional Study in a Spanish Hospital

Abstract: (1) Background: To describe sleep quality, eating behaviour and alcohol, tobacco and illicit drug use among healthcare staff in a Spanish public hospital. (2) Methods: Cross-sectional descriptive study examining sleep quality (Pittsburg Sleep Quality Index), eating behaviour (Three Factor Eating Questionnaire (R18)), tobacco and drug use (ESTUDES questionnaire) and alcohol use (Cut down, Annoyed, Guilty, Eye-opener). (3) Results: 178 people, of whom 87.1% (155) were women, with an average age of 41.59 ± 10.9 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Therefore, it appears that healthy habits could have a positive impact on mental health of HCP even in this overwhelming period of maximum stress such it was suggested by Tovani-Palone et al [ 29 ] in an article about the importance of healthy habits during the COVID-19 pandemic for general populations. These results are interesting, because a Spanish cross-sectional study about life habits of HCP during the third wave of COVID-19 found changes in sleep quality, eating behavior, and unhealthy habits such an increase of alcohol, tobacco, and drug consumption [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it appears that healthy habits could have a positive impact on mental health of HCP even in this overwhelming period of maximum stress such it was suggested by Tovani-Palone et al [ 29 ] in an article about the importance of healthy habits during the COVID-19 pandemic for general populations. These results are interesting, because a Spanish cross-sectional study about life habits of HCP during the third wave of COVID-19 found changes in sleep quality, eating behavior, and unhealthy habits such an increase of alcohol, tobacco, and drug consumption [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are interesting, because a Spanish cross-sectional study about life habits of HCP during the third wave of COVID-19 found changes in sleep quality, eating behavior, and unhealthy habits such an increase of alcohol, tobacco, and drug consumption. 30 Several strengths should be noted. First, the recruitment process, based on on-line questionnaires allowed us to study health personnel from different places of Spain from the beginning of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation